On the UV compactness and morphologies of typical Lyman α emitters from z ∼ 2 to z ∼ 6. Issue 4 (9th February 2018) - Paulino-Afonso, Ana; Sobral, David; Ribeiro, Bruno; Matthee, Jorryt; Santos, Sérgio; Calhau, João; Forshaw, Alex; Johnson, Andrea; Merrick, Joanna; Pérez, Sara; Sheldon, Oliver
Abstract: We investigate the rest-frame UV morphologies of a large sample of Lyman α emitters (LAEs) from z ∼ 2 to z ∼ 6, selected in a uniform way with 16 different narrow and medium bands over the full COSMOS field. We use 3045 LAEs with Hubble Space Telescope coverage in a stacking analysis and find that they have M UV ∼ −20, below $M_UV^*$ at these redshifts. We also focus our analysis on a subsample of 780 individual galaxies with i AB < 25 for which galfit converges for 429 of them. The individual median size ( r e ∼ 1 kpc), ellipticities [slightly elongated with ( b / a ) ∼ 0.45], Sérsic index (disc-like with n ≲ 2), and light concentration (comparable to that of disc or irregular galaxies, with C ∼ 2.7) of LAEs show mild evolution from z ∼ 2 to z ∼ 6. LAEs with the highest rest-frame equivalent widths (EWs) are the smallest/most compact ( r e ∼ 0.8 kpc, compared to r e ∼ 1.5 kpc for the lower EW LAEs). When stacking our samples in bins of fixed Lyα luminosity and Lyα EW, we find evidence for redshift evolution in n and C, but not in galaxy sizes. The evolution seems to be stronger for LAEs with 25 < EW < 100 Å. When compared to other star-forming galaxies (SFGs), LAEs are found to be smaller at all redshifts. The difference between the two populations changes with redshift, from a factor of ∼1 at z ≳ 5 to SFGs being a factor of ∼2–4 larger than LAEs for z ≲ 2. This means that at the highest redshifts, where typical sizes approach those of LAEs, the fraction of galaxies showing Lyα in emission (and with a high Lyα escape fraction) should be much higher, consistent with observations.